2023
DOI: 10.11336/jjcrs.14.1
|View full text |Cite
|
Sign up to set email alerts
|

TMS and neocortical neurons: an integrative review on the micro-macro connection in neuroplasticity

Abstract: Tian D, Izumi S. TMS and neocortical neurons: an integrative review on the micro-macro connection in neuroplasticity. Jpn J Compr Rehabil Sci 2023; 14: 1-9. Neuroplasticity plays a pivotal role in neuroscience and neurorehabilitation as it bridges the organization and reorganization properties of the brain. Among the numerous neuroplastic protocols, transcranial magnetic stimulation (TMS) is a well-established non-invasive protocol to induce plastic changes in the brain. Here, we review the findings of four pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Although the evidence regarding SICF modulation by rTMS is highly inconsistent ( Fitzgerald et al, 2006 ), we found it intriguing that SICF-I3 was suppressed by AP-iTMS. As the ISI of SICF-I3 is approximately 4.5 ms, which is approximately ~3 synapse conduction time ( Ziemann, 2020 ; Tian and Izumi, 2022b ; Tian and Izumi, 2023 ), the results suggest that the facilitation from paired-pulse SICF-I3 might be generated from longer neuron chains with multiple synapses, with the neurons on the chain bearing more inhibition from local INs ( Peurala et al, 2008 ). This effect can become greater if the I3 circuitry is specifically targeted by AP-iTMS.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although the evidence regarding SICF modulation by rTMS is highly inconsistent ( Fitzgerald et al, 2006 ), we found it intriguing that SICF-I3 was suppressed by AP-iTMS. As the ISI of SICF-I3 is approximately 4.5 ms, which is approximately ~3 synapse conduction time ( Ziemann, 2020 ; Tian and Izumi, 2022b ; Tian and Izumi, 2023 ), the results suggest that the facilitation from paired-pulse SICF-I3 might be generated from longer neuron chains with multiple synapses, with the neurons on the chain bearing more inhibition from local INs ( Peurala et al, 2008 ). This effect can become greater if the I3 circuitry is specifically targeted by AP-iTMS.…”
Section: Discussionmentioning
confidence: 92%
“…For LICF, empirical evidence regarding its mechanisms is still lacking. However, as proposed in our previous model LICF might be related to the timing-dependent inhibition-excitation shift of chandelier cells (ChCs, a subtype of cortical INs) on the postsynaptic neurons (Woodruff et al, 2011;Tian and Izumi, 2022b;Tian and Izumi, 2023). For INs, based on quantitative proportion (Rudy et al, 2011;Bakken et al, 2021), two main IN subtypes related to intracortical inhibition are included in the model, being the basket cells (BCs) and ChCs.…”
Section: Itms Neurocytological Mechanism Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…D. Tian and S.I. Izumi (17) conducted studies of neuroplasticity and determined the main aspects of microand macrocommunication. The main properties of neural networks were determined, but during the research little attention was paid to the recovery processes in diseases and their importance for medicine, especially in severe cases.…”
Section: Implications For Healing and Resiliencementioning
confidence: 99%